1998
DOI: 10.1002/pro.5560070121
|View full text |Cite
|
Sign up to set email alerts
|

How many membrane proteins are there?

Abstract: One of the basic issues that arises in functional genomics is the ability to predict the subcellular location of proteins that are deduced from gene and genome sequencing. In particular, one would like to be able to readily specify those proteins that are soluble and those that are inserted in a membrane. Traditional methods of distinguishing between these two locations have relied on extensive, time-consuming biochemical studies. The alternative approach has been to make inferences based on a visual search of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
109
0

Year Published

1998
1998
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(115 citation statements)
references
References 11 publications
3
109
0
Order By: Relevance
“…Comparable results have been found by many investigators in whole-genome surveys of yeast and other completely sequenced genomes (Arkin et al, 1997;Boyd et al, 1998;Gerstein, 1997Gerstein, , 1998bGerstein & Hegyi, 1998;Goffeau et al, 1993;Jones, 1998;Rost, 1996;Rost et al, 1995;Tomb et al, 1997;Wallin & von Heijne, 1998). In particular, our membrane-prediction program, which predicted whether a protein had transmembrane helices, indicated that 22% of the proteins in the yeast genome were integral membrane (T) proteins (those with more than one transmembrane helix).…”
Section: Figure 4 -Priorssupporting
confidence: 67%
See 1 more Smart Citation
“…Comparable results have been found by many investigators in whole-genome surveys of yeast and other completely sequenced genomes (Arkin et al, 1997;Boyd et al, 1998;Gerstein, 1997Gerstein, , 1998bGerstein & Hegyi, 1998;Goffeau et al, 1993;Jones, 1998;Rost, 1996;Rost et al, 1995;Tomb et al, 1997;Wallin & von Heijne, 1998). In particular, our membrane-prediction program, which predicted whether a protein had transmembrane helices, indicated that 22% of the proteins in the yeast genome were integral membrane (T) proteins (those with more than one transmembrane helix).…”
Section: Figure 4 -Priorssupporting
confidence: 67%
“…The values from the scale for amino acids in a window of size 20 were averaged, and then compared against a cutoff value. We used the Boyd and Beckwith MaxH criteria to set the cutoffs as in previous analyses (Boyd et al, 1998;Klein et al, 1985;Gerstein et al, 2000).…”
Section: Tms1mentioning
confidence: 99%
“…1D). Thus, we could not verify that more complex organisms need larger fractions of membrane proteins (Goffeau et al 1993;Boyd et al 1998;Wallin and von Heijne 1998). The discrepancy probably resulted from the insufficient amount of human and fly data available earlier.…”
Section: Prediction-based Classifications Of Proteomesmentioning
confidence: 88%
“…In contrast, helical membrane proteins are relatively easy to identify by bioinformatics. How many helical membrane proteins are in a genome (Goffeau et al 1993;Boyd et al 1998;Wallin and von Heijne 1998)? Is the fraction of helical membrane proteins constant, or does the fraction of helical membrane proteins correlate with the complexity of the organism (Wallin and von Heijne 1998)?…”
mentioning
confidence: 99%
“…computational protein design | protein conformational stability | membrane protein modeling | signal transduction | synthetic biology M embrane proteins represent around 30% of currently sequenced genomes and are critical in the regulation of cell signaling and cell-cell communication (1,2). When dysfunctional, however, these proteins can be responsible for serious diseases and constitute more than 60% of current drug targets.…”
mentioning
confidence: 99%